Thailand Beyond the Crisis - Warr, Peter (Rethinking Southeast Asia, 2005)
Thailand Beyond the Crisis includes recent research to give an accurate and up to date picture of the status of Thailand's economic recovery. The Asian economic crisis began in Thailand and ended a decade of sustained economic boom. This book identifies the role of policy errors involving both the Thai government and the IMF that lead to the crash of the fastest growing economy in the world. Warr addresses the consequences of the crisis, including sharply increased poverty incidence and a backlog of non- performing loans which clogged the banking system, delaying recovery. Key content includes: * the Social Consequences of the crisis, and alternatives * public sector reform * implications of a floating exchange rate * education * urbanisation and the environment. Peter Warr is currently John Crawford Professor of Agricultural Economics at the Australian National University 'All the essays are well-balanced, carefully argued, with introductory overviews and conclusions ... Mr Warr's scholarly effort is to be commended; the volume could well serve as a core textbook for a course of modern Thai studies.' - Asian Affairs Contributors Preface Note on referencing of Thai names Map of Thailand Part 1 Background to the Crisis and the Recovery Process 1. Boom, Bust and Beyond 2. Anatomy of the Crisis Part 2 The Social and Political Context of the Recovery Process 3. Pluto-Populism: Thaksin and Popular Politics 4. Socio-economic Consequences of the Crisis 5. Developing Social Alternatives: Walking Backwards into a Khlong Part 3 The New Environmenta for Economic Policy Making 6. Public Sector Reform: A Post-crisis Opportunity 7. Dealing with Debt: NPLs and Debt Restructuring 8. The Implications of a Flexible Exchange Rate Part 4 The Long Term - Human Capital, Urbanization and the Environment 9. Education: The Key to Long Term Recovery? Sirilaksana Khoman 10. Urbanization: New Drivers, New Outcomes Douglas Webster 11. Natural Resources and the Environment Mingsarn Kaosa-ard Index